Ira sleeps over - Waber, Bernard (Boston : Houghton Mifflin, 2000)
I was invited to sleep at Regine's house. Was I happy! I had never slept at a friend's house before.
TR/PS
Keywords: Sleepover -- Fiction; Children stories